The Retrieval Practice Hypothesis in Research on Learning by Teaching: Current Status and Challenges - Kobayashi, Keiichi (Frontiers in Psychology, 2022)
To explain why students learn effectively by teaching, explaining to others in particular, Koh et al. (2018 [The learning benefits of teaching: A retrieval practice hypothesis. Applied Cognitive Psychology, 32(3), 401–410]) advanced the retrieval practice hypothesis, which attributes the learning benefits entirely to the effect of practicing retrieval, that is, effortfully recalling to-be-taught information for the provision of instructional explanations. After delineating the rationale behind the retrieval practice hypothesis, the current situation of research, and the limitations of the existing approach, this paper proposes three tests for the evaluation of the hypothesis that address (1) whether explaining to others after initial studying surpasses restudying in learning performance, (2) whether the amount of effort to retrieve to-be-taught information from memory moderates the learning effects of explaining to others, and (3) whether the degree of elaboration during retrieval practice positively predicts the outcomes of learning by merely recalling to-be-taught information. Evidence is examined regarding whether each test is passed, and future directions for research on the retrieval practice hypothesis are discussed.